(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
D1S80 is a highly informative variable number of tandem repeat (VNTR) marker located in the telomeric region of chromosome 1 at 1p36-p35. Since its discovery, the D1S80 locus has been used widely in determining the origins and genetic relations among and between various populations worldwide. Here, we studied the allele frequencies and other population genetic parameters at the D1S80 locus among individuals from four major tribal populations in Bangladesh (Santal, Garo, Monipuri and Khasia). The data was then compared with the other populations including the mainstream Bengali population. A total of 31 different alleles were detected with repeat unit numbers ranging between 14 and 50. D1S80 allele with 18 repeats was the most frequent in three populations except the Santals, in which allele with 19 repeats was the most common. Observed heterozygosity was less than the expected in all four populations. Pair-wise observed genetic distances were, in general, more between the tribal populations and the mixed mainstream Bangladeshis compared to the distances between the tribal populations. Comparison of D1S80 allelic frequency distribution among seventy-six different populations placed the tribal populations along with the mainstream mixed Bangladeshis, Tamils and mixed Panjabi Indians in a clade separated from the rest. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 386-393